Pengawasan Pemerintah Daerah Terhadap Tambak Udang Berdasarkan Pasal 71 UU PPLH di Kecamatan Gumukmas - Lidang Mampetua Siahaan; Fauziyah Fauziyah (Empat Sembilan Publisher, 2026)
Shrimp farming activities in Gumukmas District, Jember Regency, provide economic benefits but raise issues of environmental pollution that harm coastal communities. This study aims to analyze the implementation of supervision by the Regional Government based on Article 71 of Law Number 32 of 2009 and to examine the relevance of applying the Good Environmental Governance (GEG) principles in the management of these shrimp farms. This study uses a mixed-methods legal research approach with a statutory approach and a conceptual approach. Empirical data were obtained through public documentation studies and digital tracking of the escalation of environmental conflicts in the field. Research results show that the implementation of supervision has not been effective because the relevant agencies tend to apply a passive supervision model (complaint-based supervision). This condition indicates administrative omission and maladministration regarding the existence of illegal ponds. In addition, the GEG principle has not been optimally applied, as seen from the closed access to licensing documents and minimal local community participation, thus violating citizens' constitutional rights to a good and healthy environment.